(untitled) (Journal of School Administration Research and Development, 2020)
This study examines teachers’ and administrators’ use of data to inform their practice in one south-central state. Using a qualitative research approach, the study involved 76 educators representing eight school districts. Data were collected using focus groups with teachers and in-depth interviews with school principals. Data were inductively and deductively analyzed using multiple cycles of coding. Analysis of data revealed three themes that exposed differences in the use of data by teachers and administrators: the challenges of data use, the “levels” at which data are viewed (micro and macro lenses), and the value placed on formal and informal data. Findings suggest that by understanding the differences between teachers’ and administrators’ perspectives on data use and recognizing the common ground that unites their perspectives, schools can create data cultures that foster shared expectations, collaboration, and trust between teachers and administrators.